2010
DOI: 10.1007/s00540-010-0967-5
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery spasm occurring in the setting of the oculocardiac reflex

Abstract: The oculocardiac reflex (OCR) occurs in up to 90% of ophthalmological surgeries. Several preventive and treatment strategies have been described. Coronary artery spasm (CAS) plays an important role in the pathogenesis of variant angina and myocardial infarction. We describe an unusual case of a perioperative myocardial infarction due to CAS that occurred in the setting of the treatment of the OCR. We offer insight aimed at minimizing the deleterious effects of the OCR and its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
6
0
2
Order By: Relevance
“…Regional anesthesia, vasopressors, hyperventilation, hypotension, and inadequate depth of anesthesia were noted as major contributing factors. Sidi et al [1] also reviewed CAS in detail and found results very similar to those of Chang et al In addition to the traditional contributing factors already mentioned, oculocardiac reflex [3], anaphylaxis [4,5], carotid sinus stimulation [6], neurological procedures [7][8][9], rocuronium [10], dolasetron [11], prostaglandin E 1 , and beta-adrenergic blockade [12] are also recently reported factors.…”
Section: Discussionsupporting
confidence: 56%
“…Regional anesthesia, vasopressors, hyperventilation, hypotension, and inadequate depth of anesthesia were noted as major contributing factors. Sidi et al [1] also reviewed CAS in detail and found results very similar to those of Chang et al In addition to the traditional contributing factors already mentioned, oculocardiac reflex [3], anaphylaxis [4,5], carotid sinus stimulation [6], neurological procedures [7][8][9], rocuronium [10], dolasetron [11], prostaglandin E 1 , and beta-adrenergic blockade [12] are also recently reported factors.…”
Section: Discussionsupporting
confidence: 56%
“…Bulgular genellikle hipotansiyon, ritim sorunları gibi belirsizdir ve ST değişikliklerini ameliyat odası koşulların-da yorumlamak güçtür. Yayınlarda adrenerjik ajanlara (efedrin, metaraminol, adrenalin) bağlı vazospazm ya da doğrudan cerrahi uyaranla oluştuğu gözlenmiştir (7)(8)(9) . Bir olguda ise göz cerrahisi sırasında hiçbir EKG değişikliği olmaksızın PMI oluşmuştur (9) .…”
Section: Discussionunclassified
“…Yayınlarda adrenerjik ajanlara (efedrin, metaraminol, adrenalin) bağlı vazospazm ya da doğrudan cerrahi uyaranla oluştuğu gözlenmiştir (7)(8)(9) . Bir olguda ise göz cerrahisi sırasında hiçbir EKG değişikliği olmaksızın PMI oluşmuştur (9) . Bradikardi dışında sorunsuz bir ameliyat sürecinin ardından, akciğer ödemi gelişen hastada artmış troponin değerleri ile tanıya varılmıştır.…”
Section: Discussionunclassified
“…Furthermore, these horses can develop intra‐anesthetic cardiac dysrhythmias (bradyarrhythmias) or arrest caused by vagal nerve stimulation during surgery . This phenomenon can be explained by the oculocardiac reflex, which is a known complication in ophthalmic surgery both in humans and in horses . The oculocardiac reflex in humans was first mentioned in 1908 by both Aschner and Dagnini .…”
Section: Introductionmentioning
confidence: 99%
“…3 This phenomenon can be explained by the oculocardiac reflex, which is a known complication in ophthalmic surgery both in humans and in horses. [4][5][6][7] The oculocardiac reflex in humans was first mentioned in 1908 by both Aschner and Dagnini. 8,9 This reflex is caused by intense ocular manipulation and is mediated by a trigeminal-vago-vagal reflex via fibers originating from the ophthalmic nerve.…”
Section: Introductionmentioning
confidence: 99%